Class and Community in Provincial Ireland, 1851-1914 - Casey, Brian (Springer International Publishing, 2018)
This book explores the experience of small farmers, labourers and graziers in provincial Ireland from the immediacy of the Famine until the eve of World War One. During this period of immense social and political change, they came to grips with the processes of modernisation. By focusing upon east Galway, it argues that they were not an inarticulate mass, but rather, they were sophisticated and politically aware in their own right. This study relies upon a wide array of sources which have been utilised to give as authentic a voice to the lower classes as possible. Their experiences have been largely unrecorded and this book redresses this imbalance in historiography while adding a new nuanced understanding of the complexities of class relations in provincial Ireland. This book argues that the actions of the rural working class and nationalists has not been fully understood, supporting E.P. Thompson's argument that 'their aspirations were valid in terms of their own experiences'.